Knowledge is of two kinds - Ngwasiri, Clement N (Technical Centre for Agricultural and Rural Cooperation, 1995)
Ignored for many decades, the role of indigenous knowledge in providing the basis for a sustainable approach to development is now being recognized in many countries. The international knowledge systems that have dominated the development agenda,...